MULTIBACILLARY LEPROSY IN TWO ADULT PATIENTS: A CASE REPORT WITH PERIPHERAL NERVE INVOLVEMENT - Rilliani Hastuti; Indri Widya Sari; Nurita Bangun Hutahean; Lilis Khairani; Ahmad Ghiffari; Thia Prameswarie (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2026)
Multibacillary leprosy remains a significant public health issue due to its potential to cause progressive nerve damage, disability, and ongoing transmission if not detected and treated early. This case report highlights two cases that underscore key lessons in leprosy management. In Case 1, despite the patient completing multidrug therapy (MDT) and being declared cured, the re-emergence of skin lesions raised the possibility of relapse, reinfection, or leprosy reaction, emphasizing the importance of post-MDT follow-up for patients. Meanwhile, Case 2 illustrates the need for early detection of peripheral neuropathy in patients with neuropathic ulcers without pain, leading to the loss of protective sensation. Peripheral nerve involvement in both cases underscores the need for thorough neurological evaluation to prevent permanent disability. The specific clinical lesson is that in-depth neurological evaluation and continuous post-MDT monitoring are crucial for preventing nerve complications and early relapse detection, thereby improving patient quality of life.